Intermarriage from Central Europe to Central Asia: mixed families in the age of extremes - Edgar, Adrienne Lynn; Frommer, Benjamin (University of Nebraska Press, 2020)
"Edgar and Frommer bring together international and interdisciplinary scholarship to analyze interethnic and interracial marriage in Eastern Europe, the former Soviet Union, and Central Asia"--
Includes bibliographical references and index
Keywords: Geschichte 1871-2013; Interethnische Ehe; Mittelasien; USA; Osteuropa; Mitteleuropa